2018
DOI: 10.1093/neuonc/noy053
|View full text |Cite
|
Sign up to set email alerts
|

Validation of postoperative residual contrast-enhancing tumor volume as an independent prognostic factor for overall survival in newly diagnosed glioblastoma

Abstract: Postsurgical, residual contrast-enhancing disease significantly negatively influences survival in patients with newly diagnosed GBM treated with chemoradiation with or without concomitant experimental therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…Another possible explanation regards the secretion rate by different subpopulations of GBM cells. It is possible to speculate that the global concentration in plasma is consequence of nonhomogeneous release of extracellular vesicles by different subpopulations, thus making the global concentration not related to markers or tumor/necrosis size (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation regards the secretion rate by different subpopulations of GBM cells. It is possible to speculate that the global concentration in plasma is consequence of nonhomogeneous release of extracellular vesicles by different subpopulations, thus making the global concentration not related to markers or tumor/necrosis size (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the impact of maximal CE resection and MGMT promoter methylation status in a homogenous IDH-wildtype glioblastoma population ( n = 175) and showed that both were significantly associated with longer overall survival ( 2 ). Ellingson et al showed in 1,054 glioblastoma patients (with partially available data on IDH mutation and MGMT methylation) that smaller residual CE tumor volumes (<12 cm 3 ) and MGMT methylation were significantly associated with longer overall survival in patients receiving chemoradiation ( 18 ). A recent study published by Molinaro et al confirmed the association between maximal CE resection and overall survival across all molecular subgroups of glioblastoma ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast enhanced T1-weighted digital subtraction maps were created in order to isolate the areas of contrast enhancement and negate blood products within tumor regions of interest. The process of generating T1 subtraction maps has been detailed previously 123 125 . Briefly, T1 weighted images with and without contrast were co-registered using affine registration (12 degrees-of-freedom; correlation coefficient cost function, FSL (FLIRT;FMRIB Software Library, Oxford, England).…”
Section: Methodsmentioning
confidence: 99%